The role of greener innovations in promoting financial inclusion to achieve carbon neutrality: An integrative review - Mohsen Brahmi; Luca Esposito; Anna Parziale; Karambir Singh Dhayal; Shruti Agrawal; Arun Kumar Giri; Nguyen Thi Loan (Economies, 2023)
In recent times, the green transition, by promoting carbon neutrality, has become highly imperative to meet environmental challenges. The present literature review study seeks to explore the intersecting role of greener innovations in facilitating financial inclusion for a sustainable future. Within the global agenda is the goal of carbon neutrality, with the aim of reducing environmental impact and mitigating climate change. Aim: The present study aims to investigate the role that technological innovations play in the financial inclusion of achieving climate neutrality. Method: Through a systematic literature review, we investigate how new innovations generate new investment opportunities and promote sustainable development. However, fair, accessible, and inclusive financing is crucial. Findings: the analyzed documents in this study shows that technological innovations can play an important role in financial inclusion for carbon neutrality and provide some important policy implications. Indeed, a favorable regulatory environment could generate positive effects already in the short term, with important environmental, economic, and social repercussions.
Keywords: 330; carbon neutrality; greener innovations; mitigating climate change; financial inclusion; sustainable development; economic